Importance of moth species as pests on pomegranate and persimmon crops in the Valencian Community (Spain) - García-Martínez, Omar; Pérez-Hedo, Mertixell; Urbaneja, Alberto; Beltrán, Victoria; Bartual, Julián; Beitia, Francisco J. (2018)
Pomegranate (Punica granatum L.) and persimmon had been traditionally considered as minor crops in Spain. However, the production of both crops has exponentially increased in the Valencian Community (eastern Spain) during the last 20 years and today they represent two economically important products in the region. There are several species of moths (Insecta: Lepidoptera) which are attacking both crops: the larvae of these species feed on the fruits and causes economical damages to producers. The most important species for both crops seemed to be Cryptoblabes gnidiella (Millière) (Lepidoptera: Pyralidae), which is a well known pest on other crops, as in citrus, and now is also attacking pomegranate and persimmon. But also there are other lepidopteran species which could represent a serious problem to both crops. In this work we have analyzed the evolution of C. gnidiella throughout a year in the two crops but also identified other lepidopteran species with economic importance. To this purpose, pheromone traps were used in several plots of pomegranate and persimmon in order to detect the dynamics of these pests. And also, the relation between the pests and their final damage to the crops were studied. C. gnidiella has shown to be the most important moth pest on pomegranate, although another species, Ectomyelois ceratoniae, has been also detected. But in contrast, in the case of persimmon, another species appears to produce similar or higher damage than C. gnidiella: Anatrachyntis badia.